Implementasi Personal Branding Dalam Meningkatkan Kredibilitas Jiwa Entrepreneurship Di Era Digital (Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
Personal branding is a process of forming public perceptions of aspects owned by individuals, including personality, abilities, values, and stimuli that produce positive perceptions in society, so that they can be used as marketing tools. An entrepreneur really needs good personal branding to build public charm towards themselves so that someone can manage their own life without having to depend on other people. This personal branding is seen from the online representation shown, both spread on websites and social media. The existence of this personal branding can help one’s self-confidence and self-control in achieving achievements as well as self-image that is built through competence and quality possessed.